Talk is chief : leadership, communication, and credibility in a high-stakes world - Modzelewski, Jack (New York : Rosetta Books, 2019)
"With compelling stories and strategies, Talk is Chief inspires leaders to treat their daily communication practices as seriously as their fiscal, operational, value creation, deal making, business transformation, and other executive responsibilities. Leaders today spend up to 90 percent of each day communicating to make good things happen in their organizations. They communicate with colleagues, customers, shareowners, creditors, regulators, advocates, and competitors. They influence culture, opportunity, risk-taking, and risk aversion. Jack Modzelewski's thirty-five years of experience working with many Fortune 500 companies as a communications consultant suggests that too many leaders undervalue and therefore underperform their vital communication responsibilities. They do so at their own disadvantage and sometimes peril in this age of heightened activism, transparency, disruption, disinformation, and crisis. Whether they recognize it or not, leaders are chief credibility officers, with organizational reputation often resting on their words and actions, especially in times of crisis. Talk is Chief provides sound advice, examples, and even a "10 Commandments of Crisis Management," so that leaders can either avoid crises or avert worst-case scenarios when an existential threat confronts them. Leadership communication today--the ability for leaders to be heard and clearly understood above the constant noise of the complicated worlds in which they must lead or govern--is of the highest importance. The stakes in this new communication environment are high and it's proven that effective leadership communication inspires people to perform collectively better, leading to better outcomes. Which is why Talk is Chief is a must-read for 21st century leaders"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Communication in management; Communication in organizations; Leadership